Universal Banks and Relationships with Firms - Ralf Elsas; Jan Pieter Krahnen (Goethe University Frankfurt, Center for Financial Studies (CFS), 2003)
Some of the most widely expressed myths about the German financial system are concerned with the close ties and intensive interaction between banks and firms, often described as Hausbank relationships. Links between banks and firms include direct shareholdings, board representation, and proxy voting and are particularly significant for corporate governance. Allegedly, these relationships promote investment and improve the performance of firms. Furthermore, German universal banks are believed to play a special role as large and informed monitoring investors (shareholders). However, for the very same reasons, German universal banks are frequently accused of abusing their influence on firms by exploiting rents and sustaining the entrenchment of firms against efficient transfers of firm control. In this paper, we review recent empirical evidence regarding the special role of banks for the corporate governance of German firms. We differentiate between large exchange-listed firms and small and medium sized companis throughout. With respect to the role of banks as monitoring investors, the evidence does not unanimously support a special role of banks for large firms. Only one study finds that banks' control of management goes beyond what non-bank shareholders achieve. Proxy-voting rights apparently do not provide a significant means for banks to exert management control. Most of the recent evidence regarding small firms suggests that a Hausbank relationship can indeed be beneficial. Hausbanks are more willing to sustain financing when borrower quality deteriorates, and they invest more often than arm's-length banks in workouts if borrowers face financial distress.
urn:nbn:de:hebis:30-10254
Keywords: G21; G32; 330; relationship lending; Hausbank; universal banking; corporate finance; corporate governance